The effect of the animation film "Nussa" towards improving the character of courtesy of children with down syndrome - Wilda Famy Delia; Isti Rusdiyani; Ratih Listyaningtyas (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This study aims to improve the ability to improve the character of courtesy of children with Down syndrome by using the video animation media Nussa on students of class VII syndrome in SKH Sutmaemun, Serang Regency. The purpose of this study is seen from the ability of students before and after the implementation of Nussa animation based on Nussa animation video criteria, namely increasing the character of courtesy towards students. This research method is an experiment with a Single Subject Research (SSR) type of study with an A-B-A design. The subject of this study was a student of class VII in the SKh Sutmaeun district of Serang. Data collection techniques by means of tests and observations. Data analysis in this study used descriptive statistical analysis. The results showed that the use of Nussa animation media could improve the character of class VII down syndrome in the Serang regency. This is indicated by (1) Increasing the Mean Level of phase A1 to phase A2 which is 33.33% to 54.165%, and (2) Changes in the stability of the data in each phase show stable data (100%) and show the ascending direction from phase A1 to A2, (3) there is a change in the level of data between the A1 / B phases (+ 33.33%) and between the B / A2 phases (-33.33%), (4) the percentage of overlap data obtained is 25% in the phase B / A2, and (5) students feel happy learning to use Nussa animated videos because they are not boring.